Pengendalian Kualitas Proses Penetasan Telur Ayam Broiler Menggunakan Pendekatan Six Sigma Guna Meminimalisir Cacat Produk: Studi kasus pada Departemen Produksi PT Super Unggas Jaya - Muhammad Alifudin Islami; Misbach Munir (MES Management Journal, 2025)
This study analyzed the causes of rejects in broiler egg production using the Six Sigma DMAIC method. Seven main types of defects were found: Miss (18.52%) caused by the parent being too old, Thin (13.74%) due to lack of vitamins and vaccines, Small (3.46%) due to the parent being too young, Dirty (8.16%) due to the parent laying eggs in the wrong place, Crack Farm (35.93%) due to the parent laying eggs in the wrong place, Crack Hatchery (12.37%) due to careless egg transfer process, and Damage (5.47%) due to damage during transfer and grading. To reduce the reject rate, the proposed actions include: paying attention to the age of the parent for Miss defects, providing vitamins and vaccinations for Thin defects, ensuring the parent is old enough for Small defects, ensuring the parent lays eggs in the right place for Dirty and Crack Farm defects, and tightening supervision during transfer and grading of eggs for Crack Hatchery and Damage defects. The implementation of these actions is expected to improve the quality of broiler egg production.